2021
DOI: 10.1093/rheumatology/keab193
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab as a potential trigger of inflammatory bowel disease in ankylosing spondylitis or psoriatic arthritis patients

Abstract: Objectives Real-world secukinumab gastrointestinal related adverse events (GIRAE) data as treatment for ankylosing spondylitis (AS) and psoriatic arthritis (PsA) are lacking. We aimed to achieve this through baseline evaluation of pre-existing inflammatory bowel disease (IBD), rates and predictors of GIRAE. Methods Patient electronic and paper records commencing secukinumab from ten UK hospitals between 2016–2019 were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
9
0
3
Order By: Relevance
“…In spite of the increased incidence rate of IBDs, including ulcerative colitis (UC) and CD, in the past two decades in Taiwan, the crude incidence of CD remains low at 0.47 in 100 000 population in 2015 3–6 . On the basis of the medical history and development of gastrointestinal manifestation after secukinumab therapy, IL‐17A inhibitor therapy‐induced CD was diagnosed in the present case 7 . To our knowledge, this is the first reported case of IL‐17A inhibitor therapy‐induced CD in Taiwan 8 …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In spite of the increased incidence rate of IBDs, including ulcerative colitis (UC) and CD, in the past two decades in Taiwan, the crude incidence of CD remains low at 0.47 in 100 000 population in 2015 3–6 . On the basis of the medical history and development of gastrointestinal manifestation after secukinumab therapy, IL‐17A inhibitor therapy‐induced CD was diagnosed in the present case 7 . To our knowledge, this is the first reported case of IL‐17A inhibitor therapy‐induced CD in Taiwan 8 …”
Section: Discussionmentioning
confidence: 72%
“…[3][4][5][6] On the basis of the medical history and development of gastrointestinal manifestation after secukinumab therapy, IL-17A inhibitor therapy-induced CD was diagnosed in the present case. 7 To our knowledge, this is the first reported case of IL-17A inhibitor therapy-induced CD in Taiwan. 8 Most inflammatory cytokine inhibitors such as IL-6, IL-1, IL-17, and IL-23 are effective against chronic systemic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 75%
“…Evidence with secukinumab has shown that the incidence of new-onset IBD is low in patients with axSpA, although these patients are more likely to develop IBD than the general population [ 73 , 74 ]. A pooled analysis of data from secukinumab randomized controlled trials showed that 13/794 patients with AS developed IBD, including ulcerative colitis in four patients (EAIR 0.2 per 100 patient-years), Crohn’s disease in eight (EAIR 0.4) and IBD undefined in one (EAIR 0.1) [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the risk of IBD development during secukinumab treatment does not increase over time [ 73 ]. Real-world data suggest that the risk of IBD development during secukinumab is higher in AS patients with a history of IBD than in those without such a history [ 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…They observed that amongst patients who developed gastrointestinal adverse events 4 had definite IBD, 7 had probable IBD while 13 had possible IBD and that all definite IBD cases had concomitant ankylosing spondylitis. Of these, two had preexisting IBD and the other two were de-novo cases, with one requiring surgical care [9].…”
mentioning
confidence: 99%